Studi Perbandingan Jumlah Eritrosit, Leukosit Dan Profil Protein Pada Cuora amboinensis Asal Bengkulu, Enggano, Aceh Dan Pengembangannya Sebagai Bahan Ajar Biologi SMA - Nengsi Juita Nengsi Juita (Fakultas Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri Kerinci, 2020)
This study aims to determine the comparison of the amount, shape and profile of C. amboinensis blood proteins from Bengkulu, Enggano, Aceh, and to determine the effectiveness of the use of Biology teaching materials for class XI IPA of SMAN 6 Kepahiang. This type of research is Research and Development analyzed in quantitative descriptive manner. Development of teaching materials refers to the modified Dick and Cerey Development model. Blood samples were taken from C. amboinensis from Bengkulu, Enggano and Aceh with 7 animals each. The results of observing leukocytes have the same shape and the results of observing erythrocyte cell forms are no different. Kruskal Wallis non-parametric statistical test results show that there is no difference in the average number of erythrocytes with p-value: 0.953. Annova test results also showed that there was no difference in the average number of leukocytes with p-value: 0.720, thus it can be concluded that C. amboinensis originating from Bengkulu, Enggano and Aceh still had a kinship relationship. Educational Research Results conclude that the use of teaching materials developed can improve student learning outcomes both in the aspects of knowledge, skills and scientific attitudes with good value criteri.